Publishing Risks - Mogens Steffensen (Risks, 2014)
“What is complicated is not necessarily insightful and what is insightful is not necessarily complicated: Risks welcomes simple manuscripts that contribute with insight, outlook, understanding and overview”—a quote from the first editorial of this journal [1]. Good articles are not characterized by their level of complication but by their level of imagination, innovation, and power of penetration. Creativity sessions and innovative tasks are most elegant and powerful when they are delicately simple. This is why the articles you most remember are not the complicated ones that you struggled to digest, but the simpler ones you enjoyed swallowing.